Functional meta-omics provide critical insights into long- and short-read assemblies. Issue 6 (27th August 2021) - Galata, Valentina; Busi, Susheel Bhanu; Kunath, Benoît Josef; de Nies, Laura; Calusinska, Magdalena; Halder, Rashi; May, Patrick; Wilmes, Paul; Laczny, Cédric Christian
Abstract: Real-world evaluations of metagenomic reconstructions are challenged by distinguishing reconstruction artifacts from genes and proteins present in situ . Here, we evaluate short-read-only, long-read-only and hybrid assembly approaches on four different metagenomic samples of varying complexity. We demonstrate how different assembly approaches affect gene and protein inference, which is particularly relevant for downstream functional analyses. For a human gut microbiome sample, we use complementary metatranscriptomic and metaproteomic data to assess the metagenomic data-based protein predictions. Our findings pave the way for critical assessments of metagenomic reconstructions. We propose a reference-independent solution, which exploits the synergistic effects of multi-omic data integration for the in situ study of microbiomes using long-read sequencing data.